2017
DOI: 10.3389/fpls.2017.00729
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Validation of Appropriate Reference Genes for Quantitative Real-Time PCR Normalization in Staminate and Perfect Flowers of Andromonoecious Taihangia rupestris

Abstract: Quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR) is the most commonly used and powerful method for gene expression analysis due to its high sensitivity, specificity, and high throughput, and the accuracy of this approach depends on the stability of reference genes used for normalization. Taihangia rupestris Yu and Li (Rosaceae), an andromonoecious plant, produces both bisexual flowers and unisexual male flowers within the same individual. Using qRT-PCR technique, investigation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 46 publications
4
34
0
Order By: Relevance
“…Unexpectedly, a novel reference gene, hnRNP, vital for the translation of mRNA in the cytoplasm [50] also showed particularly excellent stability in all sample sets. Furthermore, increasing studies in various species [51][52][53] tended to apply multiple references rather than a single one considering the reliability and accuracy for the normalization of RT-qPCR data. In our study, the combination of two reference candidate genes has already satisfied the normalization under all the experimental conditions and various tissues ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, a novel reference gene, hnRNP, vital for the translation of mRNA in the cytoplasm [50] also showed particularly excellent stability in all sample sets. Furthermore, increasing studies in various species [51][52][53] tended to apply multiple references rather than a single one considering the reliability and accuracy for the normalization of RT-qPCR data. In our study, the combination of two reference candidate genes has already satisfied the normalization under all the experimental conditions and various tissues ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…; Li et al . ); however, the identification of reference genes for the normalisation of RT‐qPCR has not been described in amaranth. This study evaluated genes to determine the most stable reference genes and analysed transcript stability of these genes in different tissues, developmental stages and under different types of stress in amaranth.…”
Section: Introductionmentioning
confidence: 99%
“…The rst three algorithms were used to evaluate the expression stability of candidate genes. Our results demonstrated that reference values and calculation methods used by the three algorithms were very different [40]. NormFinder calculates stability values based on intra-and intergroup differences [25], while geNorm compares a reference gene with all genes in a given sample to evaluate the best reference gene [24].…”
Section: Discussionmentioning
confidence: 99%